2020
DOI: 10.1101/2020.05.06.080630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Trial to test COVID-19 candidate vaccines: a case study with UISS platform

Abstract: SARS-CoV-2 is a severe respiratory infection that infects humans. Its outburst entitled it as a pandemic emergence. To get a grip on this outbreak, specific preventive and therapeutic interventions are urgently needed. It must be said that, until now, there are no existing vaccines for coronaviruses. To promptly and rapidly respond to pandemic events, the application of in silico trials can be used for designing and testing medicines against SARS-CoV-2 and speed-up the vaccine discovery pipeline, predicting an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…To get a grip on this outbreak, specific preventive and therapeutic interventions are urgently needed. In their work, Russo et al [ 1 ], present an in silico platform that showed to be in very strong agreement with the latest literature in predicting SARS-CoV-2 dynamics and related immune system host response. The computational framework they described, namely Universal Immune System Simulator (UISS), is potentially ready to be used as an in silico trial platform to predict the outcome of vaccination strategy against SARS-CoV-2.…”
Section: Topics Coveredsupporting
confidence: 58%
“…To get a grip on this outbreak, specific preventive and therapeutic interventions are urgently needed. In their work, Russo et al [ 1 ], present an in silico platform that showed to be in very strong agreement with the latest literature in predicting SARS-CoV-2 dynamics and related immune system host response. The computational framework they described, namely Universal Immune System Simulator (UISS), is potentially ready to be used as an in silico trial platform to predict the outcome of vaccination strategy against SARS-CoV-2.…”
Section: Topics Coveredsupporting
confidence: 58%
“…Computer simulation may also accelerate the search for an effective vaccine. Importantly, a study carried out at the University of Catania, in Italy, led to the development of a useful platform to predict in silico, the efficiency of selected anti-SARS-CoV-2 monoclonal antibodies in generating an adequate host immune response (101). The Universal Immune System Simulator (UISS) is able to simulate the dynamics of single entities of the immune system, following a stimulus or a therapeutic intervention, by using an agent-based methodology.…”
Section: Role Of Computational Biology In the Response To Covid-19mentioning
confidence: 99%
“… Pennisi et al (2013) and Pappalardo et al (2020) investigated the cause of chronic inflammation in relapsing remitting multiple sclerosis using AB techniques. This framework was further developed into the Universal Immune System Simulator (UISS), which is now also used to investigate immunotherapy in cancer ( Gianì et al, 2018 ) and the development of vaccines for Tuberculosis ( Russo et al, 2020b ) and Sars-Cov2 ( Russo et al, 2020a ).…”
Section: In Silico Modelingmentioning
confidence: 99%